Treatment Effects in Social Cognition and Behavior following a Theater-based Intervention for Youth with Autism. Issue 7 (3rd October 2019) - Corbett, Blythe A.; Ioannou, Sara; Key, Alexandra P.; Coke, Catherine; Muscatello, Rachael; Vandekar, Simon; Muse, Ian
ABSTRACT: This randomized clinical trial (www.clinicaltrials.gov ID# NCT02276534) examined the impact of a peer-mediated, theater-based social skills intervention, SENSE Theater®, on social cognition and behavior in 77 youth (ages 8–16) with high-functioning autism spectrum disorder. Analysis of Covariance models revealed that post-treatment, the experimental group (n = 44) performed significantly better than the controls (n = 33) on NEPSY theory of mind (verbal) subtest, demonstrated increased neural evidence of memory for faces, and engaged in more cooperative play and verbal interaction with novel peers. The study extends previous findings showing that SENSE Theater® contributes to improvement in social cognition and behavior.